(untitled) (Al-Academy, 2024)
Technologies of the theatre show elements get great transferring concerning the creative embodiment of its aesthetic elements including its raws, forms, parts and masses in an attempt to achieve the prin cipal expressive progress to embody the main theme of the idea and the intended subject .This is within the criterion of supporting the way to deal with technologies (décor elements , lighting music tones vocal affects , fashion and makeup) that achieving the emagintional appropriate atmosbheres which the writer and the director of the theatre show aim to make it present and succeed by furming active participation tunches of the ability of the cinogra . phic – element dsigners in order to invlve the theatre space atmospheres in cluding its three dim – ensions of masses ,visual elements concering what the natural delusion process has an addi-tion to the place andtime and the sequence of the drama building during the dramatic moments which contribute in developing the visual and audio events and scenes .The physical elements such as (light , colour and shadows) with the empod – yment of the vocal spheres , musical tones , fas –hion clecoration and the aesthetic of makc – up process after the current electronic technical sustems peing available which provide all of success req-uinements of the thatre show creation by its magic .artist , and aesthetic hints and harmoneyed view .Following understanding and realizing the aes – thetic values touch with its styles and direectinons to creatthe sense memory of the viwers .Accordingly , the researche found the need to search in the atudy of the subject of (the effective optic address and the vocal sustem in the theatre show ) to be the more flexible , wish and strong altern – ativeof the technical elements of the realized physical – viewed servicer presides the little coast achievement and the easiest job towards the speed of achieving the theatre production to achieve the effective optic address and the sensitive harmony by applying the current princi – ples that enjoyend by aesthetic snd knowledge add- ress from which the literary text analysis and view criterion is transferred .Building on what aforementioned , the vesearcher sees that thene is a necessity to develop the req uinements of that address and its ngagement whith the vocal system acrocc an objective analyst study hence this subject never jiven the due importance in the field of the academic studies ercept some essays and some other studieo which did not deal with the optic address and the wayto dismantle it and what it was marked by .It is the address process which joins between the optic address and process .Actuallu it his gave the research an objective justifiicalion to study this subject in an attempt to rooting the technical know ledye and explain the aesthelie affects of that address, the difficultien of the vocal system con, tribution to raise its competent to realize the aesthetic elite and thetechnical enjoyment that are quirecl for the theatre show .The researcher cdued this research ( The Effestive LAS optic result , Address and the vocal system of the theatre show.